Waste and recycling - Hewitt, Sally, 1949- (London : Franklin Watts, 2008)
Looks at how paper, organic waste, cooking oil, plastic, metal, and other substances and items can be reduced and/or recycled, features brief case studies of kids who are involved in recycling efforts, and includes activities.
Includes bibliographical references (p. 31) and index.
Booklist
Library Media Connection
Wilson's Children
6.9
3-6.
Keywords: Recycling (Waste, etc.) -- Juvenile literature; Refuse and refuse disposal -- Juvenile literature; Recycling (Waste); Refuse and refuse disposal; Recycling; Refuse and refuse disposal